Bis{N-[2-hydroxy-1,1-bis(hydroxymethyl)ethyl]glycinato-κ3O,N,O′}iron(II) - Ning Jiang (Acta Crystallographica Section E, 2014)
In the title compound, [Fe(C6H12NO5)2], the FeII ion lies on an inversion center and is coordinated by two N atoms and four O atoms from two tridentate N-[2-hydroxy-1,1-bis(hydroxymethyl)ethyl]glycine ligands, forming a slightly distorted octahedral coordination environment. In the crystal, O—H...O, O—H...N and weak C—H...O hydrogen bonds link molecules, forming a three-dimensional network.